RIBOMUNYL IN PROPHYLACTICS OF RELAPSE OF STENOSING LARYNGOTRACHEITIS - S.N. Orlova; A.I. Ryvkin ("Paediatrician" Publishers LLC, 2008)
The activity of ribomunyl in treatment and rehabilitation of 40 pediatric patients with relapsing stenosing laryngotracheitis, developed on the basis of acute respiratory viral infection was investigated. Treatment with ribomunyl recovers microbiocenose of nasopharynx and fauces, normalizes pulmonary ventilation and decreases liminal sensitivity of respiratory tract to the histamine. Key words: relapsing stenosing laryngotracheitis, ribomunyl, prophylactics, children.